(untitled) (Transport systems and technologies, 2022)
Considered method of finding energy fragments of images of laser tracks in real time and its application for image recognition problems are considered. Given theoretical information, experimental research and software implementation of the image recognition system similar to natural structures. Presented an analysis of recent work on neurobiology and work related to the modeling of neural mechanisms. The main problems in the existing work related to the modeling of information perception systems in a natural way have been identified. The aim of the study is the software application of the method of finding the energy centers of images in real time to optimize these energy centers. The task of the research is to analyze the application of the method of finding the energy centers of fragments of images of laser paths. Carried out the description of the method of analysis of images of laser tracks on the basis of determination of the center of gravity on the basis of moment signs is carried out. Described an example of work is given and the main functionality of the laser image processing program. Presented samples of reference images and individual fragments of long laser paths used in the experiments, as well as the curves of their energy centers. Shown computer simulation of laser path image processing was performed, as a result of which the adequacy of the calculated results.